Nodes of the default mode network implicated in the quality of empathic responses: a clinical perspective of the empathic response - Oliveira-Silva, Patrícia (2022)
The ability to empathize with another person's inner experience is believed to be a central element of our social interactions. Previous research has focused on cognitive (e.g., theory of mind) and emotional (e.g., emotional contagion) empathy, and less on behavioral factors (i.e., the ability to respond empathically). Recent studies suggest that the Default Mode Network (DMN) mediates individual variability in distinct empathy-related behaviors. However, little is known about DMN activity during actual empathic responses, understood in this study as the ability to communicate our understanding of the others’ experience back to them. This study used an empathy response paradigm with 28 participants (22-37 years old) to analyze the relationship between the quality of empathic responses to 14 empathy-eliciting vignettes and patterns of attenuation in the DMN. Overall, the results suggest that high levels of empathic response, are associated with sustained activation of the DMN when compared with lower levels of empathy. Our results demonstrate that the DMN becomes increasingly involved in empathy-related behavior, as our level of commitment to the other's experience increases. This study represents a first attempt to understand the relation between the capacity for responding in a supportive way to others’ needs and the intra-individual variability of the pattern of the DMN attenuation. Here we underline the critical role that the DMN plays in high-level social cognitive processes and corroborate the DMN role in different psychiatric disorders associated with a lack of empathy.